Pancake Kidney: A Rare Case Report Developmental Anomaly in Child - Bastola, Ramjee; Bhatta, Pashupati; Jha, Akhilesh Kumar; Meheta, Shekhar; Raya, Akash; Ansari, Mohammad Ashfaque (Med Phoenix, 2017)
The aim of the study is to present a rare case of incidentally detected pelvic pancake kidney with radiological imaging findings in a 11 year old male child. There are many developmental anomalies of kidney Various types of congenital renal abnormalities such as renal agenesis, ectopic or horseshoe kidney can be encountered where one of the most rarest presentation with a single ureter on pancake kidney is encountered in number that count in fingers worldwide. Med Phoenix Vol.2(1) July 2017, 71-73